Psoriasis de novo or exacerbation by PD-1 checkpoint inhibitors - Zi Wan; Jiangyuan Huang; Xiaojie Ou; Shuang Lou; Jianji Wan; Zhu Shen (Sociedade Brasileira de Dermatologia, 2024)
Abstract PD-1 (programmed Death-1) immune checkpoint inhibitors have provided significant benefits to tumor patients. However, a considerable proportion of the patients develop immune-related adverse events (irAEs), of which cutaneous irAEs (cirAEs, e.g., psoriasis) occur relatively early. This review provides an overview of the current progress in psoriasis de novo or exacerbation by PD-1 checkpoint inhibitors. It not only describes the relevant influencing factors but also theoretically analyzes the immunological mechanisms that lead to the onset or exacerbation of psoriasis. Finally, the authors present guidelines for the treatment of psoriasis de novo or exacerbation by PD-1 checkpoint inhibitors. The review is intended to assist dermatologists in the early recognition and effective individualized management of such cirAE, which is helpful to continue or adjust the tumor-targeted immunotherapy on the basis of ensuring the quality of life of tumor patients.